Multi-floor facility layout improvement using systematic layout planning and simulation - Hosseini, Seyedeh Sabereh (2013)
Every factory encounters with different layout problems from time to time and the operating efficiency of a manufacturing company is significantly influenced by its plant layout. Lack of consideration to facility planning and work flow design, as the company grows, is common. METALKUB is such a company that produces different types of cards and it is located in Iran. This company is facing with two problems in its production layout of which one of them is high distance between packaging department at first floor and pickup storage in ground floor that have high frequency of flow each day. Workers should walk through a long distance between these two departments which lead to high travelling time. Another problem is crosstraffic between some departments at first floor. The objective of this project is minimizing total traveling time, distance and number of cross-traffic. Systematic Layout Planning is employed to identify work/information flow through operation of products. Using this information, design alternative is created which decreases the travelling time and distance of the production flow. The effectiveness of proposed layout is determined using ARENA simulation academic version. Total travel distance from packaging process until keeping in warehouse is reduced significantly by 8417.5 m to 5023 m, which subsequently reduces time of travel as well. The number of cross-traffic is decreased from 38 to 24.